Production of Oil Palm Frond Fiberboard and its Sound Absorption Characteristics - Sihabut, Tanasri; Laemsak, Nikhom (Agriculture and Natural Resources, 2012)
This study investigated the sound absorption capacity of fiberboards produced from oil palm fronds treated by nine different combinations of cooking and refining processes. The percentage fiber yield, consumed energy and wastewater characteristics were also compared. The results showed that all acoustic boards had high sound absorption capacity at high frequencies. Although boards produced from fronds cooked for 21 min at 162 ± 2 ÀC and crushed by a disk refiner with clearance distance of the disk set at 0.5 mm showed the best sound absorption capacity, the fiber yield gained from this condition was the lowest and the consumed energy and biological oxygen demand were the highest. Keywords: , , , ,